An analysis of green school facility management for children with special needs in inclusive early childhood education - Katoningsih, Sri; Dwi Wardhani, Junita; Budi Hastuti, Isnaini; Asmawulan, Tri; Faizatul Fitriyah, Qonitah; Shari, Destita; Kartika Ananda (Jurnal Pendidikan Anak, 2025)
This study analyses the management of child friendly facilities and infrastructure in inclusive early childhood education. The research uses a qualitative approach, data were collected through observations of school activities and interviews with principals, teachers, and parents. The purpose of this study is to analyse the management of green school facilities in inclusive early childhood education and to identify the problems and impacts related to their implementation for children with special needs. This study uses a qualitative approach to understand in depth the management of environmentally friendly school facilities for children with special needs in inclusive early childhood education. Collecting data by observation, interview. Data analysis techniques are triangulated data and literature review. The study analyses inclusive facility management requires not only physical adaptation but also an infrastructure, supporting facilities, tools and learning media, tools, Infrastructure management, parent participation management and technology.Inclusive and eco-friendly early childhood education. Good infrastructure, supportive facilities, engaging learning tools, strong management, active parents, and smart use of technology. Classrooms should be more than just accessible they need to be green, safe, and friendly for every child’s growth. Facilities like quiet rooms, sensory spaces, and adaptive playgrounds are not luxuries but essentials for learning and healing. Teachers also need the right training to use assistive tech and eco-friendly resources effectively, while parents play a key role as partners in shaping schools. Inclusive education offers a fresh framework that supports global goals for quality education and sustainable communities.